INVESTIGATING THE ROLE OF FCER1A GENE (RS2251746) POLYMORPHISMS AND INTERLEUKIN-6 LEVELS IN ABORTION RISK AMONG WOMEN WITH BLOOD ALLERGIES - Nawres Adnan Abdulameer; Ibtissem Ben Amara (Journal for Technology and Science, 2026)
Objective: We examined the correlation between functional polymorphisms in the high-affinity IgE receptor alpha chain gene (FCER1A), serum interleukin-6 (IL-6) concentrations, and the risk of RSA. Method: This case-control research comprised 185 women with idiopathic recurrent pregnancy loss (≥2 successive pregnancy losses) and 190 ethnically matched controls who had successful pregnancies. Genotyping of FCER1A polymorphisms (rs2251746). Serum IL-6 concentrations were quantified using ELISA. Relationships among genotypes, IL-6 concentrations, and clinical attributes were examined. Results: The FCER1A rs2251746 T allele exhibited a significant association with heightened RSA risk (OR=2.37, 95% CI: 1.69-3.31, p<0.001). The heterozygous (CT) and homozygous (TT) genotypes gave a 2.40-fold and 4.80-fold higher risk, respectively. Serum IL-6 concentrations were markedly increased in RSA patients relative to controls (6.84±2.31 vs. 3.62±1.47 pg/mL, p<0.0015). Genotypes Rs2251746 exhibited a significant correlation with IL-6 levels, demonstrating a steady increase from CC to TT genotypes in both RSA patients (p<0.0019) and controls (p=0.0072). In RSA patients, the TT genotype correlated with an increased incidence of pregnancy losses (p=0.0063) and an earlier gestational age at loss (p=0.0012) relative to other genotypes. Novelty: This offers fresh insights into the immunogenetic foundation of RSA and may reveal potential targets for therapeutic intervention in at-risk women.